Dietary replacement of inorganic trace minerals with lower levels of organic trace minerals leads to enhanced antioxidant capacity, nutrient digestibility, and reduced fecal mineral excretion in growing-finishing pigs - Xiong, Yunxia; Cui, Bailei; He, Zhentao; Liu, Shuai; Wu, Qiwen; Yi, Hongbo; Zhao, Fei; Jiang, Zongyong; Hu, Shenglan; Wang, Li (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the effects of dietary replacing 100% inorganic trace minerals (ITMs) with 30% 60% organic trace minerals (OTMs) on the performance, meat quality, antioxidative capacity, apparent nutrient digestibility, and fecal mineral excretion, and to evaluate whether low-dose OTMs could replace whole ITMs in growing-finishing pigs’ diets. A total of 72 growing-finishing pigs (Duroc × Landrace × Yorkshire) with an initial average body weight of 74.25 ± 0.41 kg were selected and divided into four groups with 6 replicates per group and 3 pigs per replicate. The pigs were fed either a corn-soybean meal basal diet containing commercial levels of inorganic (100% ITMs) or a basal diet with 30%, 45%, or 60% amino acids-chelated trace minerals instead of 100% ITMs, respectively. The trial ended when the pigs’ weight reached approximately 110 kg. The results showed that replacing 100% ITMs with 30% 60% OTMs had no adverse effect on average daily gain, average daily feed intake, feed/gain, carcass traits, and meat quality (P>0.05), but significantly increased serum transferrin and calcium contents (P<0.05). Meanwhile, replacing 100% ITMs with OTMs tended to increase serum T-SOD activity (0.05≤P<0.1), and 30% OTMs significantly increased muscle Mn-SOD activity (P<0.05). Moreover, replacing 100% ITMs with OTMs tended to increase the apparent digestibility of energy, dry matter, and crude protein (0.05≤P<0.1), while significantly reducing the contents of copper, zinc, and manganese in feces (P<0.05). In conclusion, dietary supplementation with 30 60% OTMs has the potential to replace 100% ITMs for improving antioxidative capacity, apparent nutrient digestibility, and reducing fecal mineral excretion without compromising the performance of growing-finishing pigs.